Preparation and thermal decomposition of solid-state cinnamates of lighter trivalent lanthanides - Carvalho Filho, M. A S [UNESP]; Fernandes, N. S. [UNESP]; Leles, M. I G; Mendes, R. [UNESP]; Ionashiro, Massao [UNESP] (Springer Nature, 2000)
Some new compounds of cinnamic acid with lighter trivalent lanthanides were prepared in the solid state. The compounds have general formula ML3·H2O, where L is cinnamate (C6H5-CH=CH-COO-) and M is La, Ce, Pr, Nd or Sm. Thermogravimetry, derivative thermogravimetry, differential scanning calorimetry, infrared absorption spectra and X-ray diffraction powder patterns were used to characterize and to study the thermal stability and thermal decomposition of these compounds.
Keywords: Absorption spectroscopy; Differential scanning calorimetry; Infrared spectroscopy; Pyrolysis; Thermodynamic stability; Thermogravimetric analysis; X ray powder diffraction; Cinnamic acid; Derivative thermogravimetry; Infrared absorption spectra; Lighter trivalent lanthanides; Solid state cinnamates; Rare earth compounds